The effect of high- vs. low-intensity training on aerobic capacity in well-trained male middle-distance runners - Enoksen, E.; Shalfawi, S. A. I.; Tonnessen, E. (The Journal of Strength and Conditioning Research, 2011)
The purpose of this study was to examine the effect of 2 different intervention training regimes on Vo2max, Vo2max velocity (vVo2max), running economy (RE), lactic threshold velocity (vLT), and running performance on a group of well-trained male middle-distance runners in the precompetition period. Twenty-six well-trained male middle-distance runners took part in the study. All participants were tested on Vo2max, vVo2max, RE, lactate threshold (LT), vLT, and a performance test. The participants were matched according to their pretest results, then randomly assigned into 1 of 2 groups, a high-volume (70 km) low-intensity training group (HVLI-group); or a high-intensity low-volume (50 km) training group (HILV-group). No significant differences were found between the 2 groups on all measures both before and after the intervention period. Furthermore, the HILV-group had a marked increase in vVo2max and vLT after the training period when compared with pretest. Both groups had a marked improvement in RE. The performance test showed that the HILV-group made 301 ± 886 m (1.0 ± 2.8 minutes) and the HVLI-group 218 ± 546 m (0.9 ± 1.8 minutes) in progress. The production of lactic acid was notably higher in the HILV-group (0.9 mmol) when compared with the pretest. The findings show that male middle-distance runners tested in this study improved in vVo2max and vLT more when they train around LT, than training with low intensity for a short period of 10 weeks.